The Lotter case : towards a discourse network of female perpetrated killing. - Stead, Morgan (My University, 2014)
This research uses trial data to extend previous research by Stead and Howard-Payne (2012) to examine discourse regarding Nicolette Lotter, a convicted female killer, and to proffer a preliminary theory of discursive networks. A discursive analytic approach to, and a Foucauldian Feminist interpretation of, the data was adopted to compare and contrast discursive constructions of the subject produced within the legal and media context in the interest of understanding how hegemonic understandings of femininity continue to be (re)produced in contemporary society. This report argues for a distinction between discursive construction and discursive practice, where the former is show to operate in production of the latter. It suggests further that the discourse produced in the legal context and the discourse produced in the media context align to fashion a discourse network where convergence occurs at the level of construction and divergence occurs at the level of practice. Such a discourse network arising in relation to Nicolette Lotter is shown to foster an understanding of the female killer which contributes to the fortification of gender prescriptions which are of patriarchal orientation in the interests of preserving male dominance and female subjugation.
Keywords: Law; Media; Female killers; Parricide; Gender; Power; Discourse; Foucauldian feminist; Lotter case